Assessment of myocardial blood perfusion improved by CD151 in a pig myocardial infarction model - Zuo Hou-juan; Liu Zheng-xiang; Liu Xiao-chun; Yang Jun; Liu Tao; Wen Sha; Wang Dao-wen; Zhang Xin (Acta Pharmacologica Sinica, 2016)
Aim: To appraise the efficacy of CD151-induced myocardial therapeutic angiogenesis in a pig myocardial infarction model. Methods: CD151 and anti-CD151 were constructed into the recombinant adeno-associated virus (rAAV) vector. All 26 pigs were subjected to coronary artery ligation or no surgery. Eight weeks after coronary artery ligation, the expression of CD151 was measured by Western blot and immunostaining. Capillary density was evaluated using immunostaining for von Willebrand factor (vWF). 13N-labeled NH3 positron emission computed tomography ([13N]NH3 PET) was measured to assess regional myocardial perfusion and the defect area. Results: CD151 gene delivery could increase the expression of CD151 at protein level. Over-expression of CD151 increased the density of total capillaries in the ischemic myocardium, significantly improved the blood perfusion and reduced the defect area percentage. Conclusion: This study demonstrated that the rAAV-mediated CD151 gene delivery promoted efficient neovascularization and increased the blood perfusion after myocardial infarction in pigs.